First-principles calculation of intrinsic defect chemistry and self-doping in PbTe. (December 2017) - Goyal, Anuj; Gorai, Prashun; Toberer, Eric; Stevanović, Vladan
Abstract Semiconductor dopability is inherently limited by intrinsic defect chemistry. In many thermoelectric materials, narrow band gaps due to strong spin–orbit interactions make accurate atomic level predictions of intrinsic defect chemistry and self-doping computationally challenging. Here we use different levels of theory to model point defects in PbTe, and compare and contrast the results against each other and a large body of experimental data. We find that to accurately reproduce the intrinsic defect chemistry and known self-doping behavior of PbTe, it is essential to (a) go beyond the semi-local GGA approximation to density functional theory, (b) include spin–orbit coupling, and (c) utilize many-bodyGW theory to describe the positions of individual band edges. The hybrid HSE functional with spin–orbit coupling included, in combination with the band edge shifts fromG 0 W 0 is the only approach that accurately captures both the intrinsic conductivity type of PbTe as function of synthesis conditions as well as the measured charge carrier concentrations, without the need for experimental inputs. Our results reaffirm the critical role of the position of individual band edges in defect calculations, and demonstrate that dopability can be accurately predicted in such challenging narrow band gap materials. Thermoelectrics: Atomic-level modeling Accurate modeling of defects in PbTe lies on the combination of hybrid functionals with spin-orbit coupling and Green function theory. Dopability of thermoelectric materials (that can convert thermal into electrical energy and vice versa) is crucial for their improvement; however most modeling approaches fail on an atomic level, especially if spin-orbit coupling effects (that modify the band position) are present. In this work, Vladan Stevanovic and coauthors manage to accurately reproduce the electronic structure of PbTe with first-principles based density functional theory. They prove that the only approach that can model the intrinsic defect chemistry, in agreement with experimental results, is the combination of hybrid functionals (based on a screened Coulomb potential) with spin-orbit coupling and the band edge shifts calculated through theG 0 W 0 approximation (which calculates the Green function theory that models excited-state properties of extended systems). Such level of understanding is necessary to predict the dopability of PbTe.